Pharmacophore Nanoarrays on DNA Origami Substrates as a Single‐Molecule Assay for Fragment‐Based Drug Discovery. Issue 45 (9th October 2018) - Kielar, Charlotte; Reddavide, Francesco V.; Tubbenhauer, Stefan; Cui, Meiying; Xu, Xiaodan; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian
Abstract: The rational combination of techniques from the fields of nanotechnology, single molecule detection, and lead discovery could provide elegant solutions to enhance the throughput of drug screening. We have synthesized nanoarrays of small pharmacophores on DNA origami substrates that are displayed either as individual ligands or as fragment pairs and thereby reduced the feature size by several orders of magnitude, as compared with standard microarray techniques. Atomic force microscopy‐based single‐molecule detection allowed us to distinguish potent protein–ligand interactions from weak binders. Several independent binding events, that is, strong, weak, symmetric bidentate, and asymmetric bidentate binding are directly visualized and evaluated. We apply this method to the discovery of bidentate trypsin binders based on benzamidine paired with aromatic fragments. Pairing of benzamidine with the dye TAMRA results in tenfold enhancement of the trypsin binding yield. Abstract : Nanoarrays of small pharmacophores are displayed on DNA origami substrates as either individual ligands or fragment pairs. Several independent protein–ligand binding events could be distinguished: strong, weak, symmetric bidentate, and asymmetric bidentate binding. Using this method, a novel benzamidine‐based bidentate trypsin binder has been discovered with a tenfold‐enhanced trypsin binding yield compared to benzamidine alone.